2016
DOI: 10.1073/pnas.1603120113
|View full text |Cite
|
Sign up to set email alerts
|

Cross-modal object recognition and dynamic weighting of sensory inputs in a fish

Abstract: Most animals use multiple sensory modalities to obtain information about objects in their environment. There is a clear adaptive advantage to being able to recognize objects cross-modally and spontaneously (without prior training with the sense being tested) as this increases the flexibility of a multisensory system, allowing an animal to perceive its world more accurately and react to environmental changes more rapidly. So far, spontaneous cross-modal object recognition has only been shown in a few mammalian … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
46
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(51 citation statements)
references
References 54 publications
5
46
0
Order By: Relevance
“…The uni-modal tests correspond with the results of fish that were trained only with the active electric sense27. Thus, electrosensory capture is independent of possible training effects, which might have influenced the results of the electrically trained fish.…”
Section: Discussionsupporting
confidence: 64%
See 3 more Smart Citations
“…The uni-modal tests correspond with the results of fish that were trained only with the active electric sense27. Thus, electrosensory capture is independent of possible training effects, which might have influenced the results of the electrically trained fish.…”
Section: Discussionsupporting
confidence: 64%
“…In an earlier study27, we showed that G. petersii, which were trained to discriminate between two objects using either only the active electric sense or only vision, were capable of spontaneous cross-modal object recognition. Furthermore, when trained only with the active electric sense, electrolocation dominated over vision during object discrimination at short range.…”
mentioning
confidence: 91%
See 2 more Smart Citations
“…The resulting changes in the transcutaneous electric field are transduced by cutaneous electroreceptors and encoded as train of spikes in primary electroreceptive afferents (Bullock et al, 1961;Fessard and Szabo, 1961;Lissmann, 1958;Szabo and Fessard, 1974;Wright, 1958). This information is further processed in the brain stem (Aumentado-Armstrong et al, 2015;Bell and Maler, 2005;Heiligenberg and Rose, 1985;Kawasaki, 2005) and telencephalon (Harvey Girard et al, 2010;Trinh et al, 2016), giving origin to reflex Post and von der Emde, 1999), stereotyped (Heiligenberg, 1991;Kawasaki, 2005;Moller, 1995) and learned behaviors (Jun et al, 2014;Schumacher et al, 2016;Walton and Moller, 2010).…”
Section: Introductionmentioning
confidence: 99%